2020
DOI: 10.3390/nu12113427
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early Programming and Early Nutrition on the Development and Progression of Celiac Disease: A Review

Abstract: Experimental and epidemiological evidence has shown that modifications of the intrauterine environment can have deleterious consequences for individuals, expressed as an increased risk of suffering non-communicable pathologies in adult life, which is known as the hypothesis of the early origin of diseases or fetal programming. On the other hand, changes in gene expression patterns through epigenetic modifications can be the basis for long-term maintenance of the effects of fetal programming. In this sense, epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 160 publications
0
9
0
Order By: Relevance
“…The individuals with Down syndrome have a higher predisposition to autoimmune diseases (2, 37), including CD (38). The up regulation of a panel of proteins and their potential as a biomarker for prenatal diagnosis and as revealing of pathogenesis of Down syndrome has also been demonstrated (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individuals with Down syndrome have a higher predisposition to autoimmune diseases (2, 37), including CD (38). The up regulation of a panel of proteins and their potential as a biomarker for prenatal diagnosis and as revealing of pathogenesis of Down syndrome has also been demonstrated (39).…”
Section: Discussionmentioning
confidence: 99%
“…The notable increase in the incidence of gastrointestinal (GI) pathologies has led to the search for a deeper understanding of the role of the GI immune system. There has been interest in the ontogeny, early growth, and development of the intestine during the prenatal stages because of its potential to play a role in gut physiology or pathological challenges in later life (1)(2)(3). Ontogenesis of the immune system begins as early as 3 weeks after conception and continues after birth and childhood (4).…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence and prevalence of CD have increased quite dramatically over the last decades, this cannot be explained by increased awareness alone (35). So far, several environmental factors have been investigated, such as the effects of early nutrition, the presence of a typical microbiota in celiac patients and antibiotic exposure in early life (37). Also, while in various genome‐wide association studies (GWAS) up to 40 non‐HLA loci have been identified as potentially related to CD (38), the effect was proven very weak.…”
Section: Present and Future Research Directions In Pediatric Gastroen...mentioning
confidence: 99%
“…The entry of gluten into the small intestine leads to painful digestive disorders, followed by in ammation of the intestinal mucosa, villous atrophy, and crypt hyperplasia (3). As a complex disease, celiac is caused by a combination of genetic and environmental factors (4). The main genetic susceptibility factors for CeD are human leukocyte antigen (HLA)-DQ2 and -DQ8 haplotypes, which account for approximately 40% of the heritability of celiac disease (5,6).…”
Section: Introductionmentioning
confidence: 99%